A genocide’s memorial in Argentinian Chaco: Memorial ao genocídio no Chaco argentino (Revista de História da UEG (REVHIST), 2024)
On July 19, 1924, a massacre began in the Napalpí Reduction (Chaco, Argentina), causing the death of hundreds of Qom and Moqoit people. The relentless persecution of the fleeing families lasted three months. Eighty years later, a group of Qom young people began to investigate the memories of their grandparents about the history of their people and especially about those events that were narrated in secret and filled with silence. The investigations of these young people managed to overcome certain assumptions to recover forgotten details and to give spatial expression to the narratives, strengthening the identification with the old territory, and especially, to express the need and the right to take the national state to trial, for which the Napalpí Foundation was created. On the eve of the centenary of the massacre, the so-called “trial for the truth” culminated and a memorial was built near one of the mass graves originating from the 1924 massacre, which includes bodies returned by the Silver Museum and that of a Malvinas fighter, all of them Qom.Keywords: Memorial, Genocide, Native peoples, Napalpí.